Analysis of coal facies and parting in The Balikpapan formation, Kutai Basin, East Kalimantan - Fauzan Roni; Listyani R.A.T.; Pambudi Setyo (E3S Web of Conferences, 2024)
The research area is located in RKBM coal mining area in East Kalimantan. One factor that influences the presence of parting in coal is the depositional environment. The existence of coal partings in this open pit area needs to be analyzed to determine the following steps in the exploration and further exploitation processes. The purpose of this study is a geological survey with the aim of knowing the coal facies and its parting characterization. The research was done by surface geological observation and drilling method. The results show that the facies association in this mining associated with delta systems such as channel, back swamp, flood plain, levee, crevasse splay, and inter distributary bay. The open pit area is composed of dominant lithology deposited in the upper delta plain environment. The presence of many and thin partings are often found in coal associated with the back swamp facies and deposited in the upper delta plain environment, which is mainly associated with fluvial systems. The distribution of parting in the study area is interpreted as not widespread because it is associated with back swamps that are affected by flood plains, and sometimes their distribution is cut off by channels.